KEPUTUSAN STRATEGIS DAN KINERJA UMKM - Amelia Setyawati (Jurnal Akademika, 2019)
Micro small medium enterprises (MSME) are the backbone of the Indonesian economy, and even the world. The purposed of this study was to test empirically the effect of strategic decisionon  performances MSME sector food and beverage industry in Bandung Raya. The research used explanatory research to clarify the relationship between the study variables and test hypotheses. The sampling technique used is random sampling propotionate area. The sample used in the study amounted to 152 owners of MSME. The results of the study are significant effect on the performances MSME of strategic decision.Keywords:Strategic Decision, performance MSME